ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PEMBIAYAAN BANK SYARIAH DI INDONESIA - Iqbal Andhi Brianto; Sugeng Hariadi; Eko Walujo Suwardyono (CALYPTRA, 2018)
This study was conducted to determine the effect of DPK, ROA, CAR, BOPO, and NPF on various financing that is Mudharabah, Musyarakah, Murabahah, Qardh, Istishna and Ijarah at two sharia commercial banks in Indonesia. This study uses data from the annual financial statements of two Islamic banks in Indonesia, namely Bank Syariah Mandiri and Bank Muamalat in the period 2007-2015. Analyzer used in this research is multiple regression. The results showed that DPK, ROA, CAR, BOPO, and NPF simultaneously affect each type of financing, namely Mudharabah, Musyarakah, Murabahah, Qardh, Istishna, Ijarah. DPK Variable Influence Positive To Mudharabah, Musyarakah, Murabaha, Qardh, and Ijarah. Negatively affect Istishna. ROA variables have positive effect on Murabahah, Qardh, Istishna, and Ijarah. But it does not affect Mudharabah and Musyarakah.Variabel CAR positive effect on Murabahah, Qardh, Istishna, and Ijarah. Negatively affected Musharaka. But it does not affect Mudharabah. BOPO variables have positive effect on Qardh. But it does not affect Mudharabah, Musyarakah, Murabahah, Istishna and Ijarah. The NPF variable has a positive effect on Musyarakah, Murabahah, Istishna and Ijarah. But negatively negatively to Mudharabah and Qardh.